What is BIBLIORCHIDEA? - Jenny, Rudolf (Lankesteriana: International Journal on Orchidology, 2015)
Literature is still playing a major role in science and research, on one side because it is a documenta- tion of research already done and a demonstration of the results. On the other hand it is also a record about recent research. At least for the time being, literature search is a part of any scientific work or project.